Lifelong commitment to ascetic life and orders: Hindu women renunciants in India - Pandya, Samta P. (Cogent social sciences, 2017)
Based on the survey of 3,699 Hindu women renunciants across six Hindu-based orders/faith-based organisations in India that encourage women’s renunciation and lifelong commitment to religious life and ascetism, this paper maps their profile, religiosity, spirituality, reasons for joining the order, fears, future plans, strategies of dealing with life in the order and strategies to enhance life quality, as well as their perceived meaning in life. Results of the logistic regression analysis showed that Hindu women renunciants with higher education and higher scores on religiosity and spirituality scales had joined the orders/FBOs by choice and personal inclination or commitment to faith and the charismatic teacher, had a greater propensity to get more involved in varied activities the orders/faith-based organisations, and perceived a higher meaning in life. Substantiating the gap of macro data on Hindu women’s renunciation, this paper then stresses on newer nuances of this form of women’s ascetism whose crux lies in challenging the prescribed cultural time-tables for women such as marriage and motherhood by emphasizing celibacy, that deem in-depth exploration.